Analysis of Blood Availability During the COVID-19 Pandemic Period in Blood Bank Dr. Wahidin Sudirohusodo Hospital - Antariksa Putra; Raehana Samad; Sri Julyani; Rachmawati Adiputri Muhiddin (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Blood Bank's challenge during the COVID-19 era is securing and protecting blood supplies even though countries aretaking precautionary measures with social distancing to prevent or reduce the number of infections caused by COVID-19.This study aimed to compare blood availability before and during the COVID-19 pandemic at the blood bank of Dr. WahidinSudirohusodo Hospital. A Descriptive-analytic study with an observational approach using the Shapiro-Wilk test todetermine the normality of the sample and the paired T-test. Sample data was taken between March-August 2019 andMarch-August 2020. A significant difference was found in blood demand (p-value=0.004), amount of blood transfusion(p-value=0.006), stock and reference report (p-value=0.005), blood service report (p-value=0.005), cito waiting time(p-value=0.002) and regular waiting time (p-value=0.016). There was no significant difference in blood indicator Packed RedCell (PRC) (p-value=0.119). The Large-Scale Social Restriction Policy (PSBB) and reduction of elective surgery in hospitalsaffect the fulfillment of Blood Bank and faster attendance time of blood during the pandemic. The decrease in a number ofblood demands during the COVID-19 pandemic affected the number of blood transfusions, blood service reports, stocks,referrals, and cito and regular waiting time services.